Tinjauan Mashlahah Imam Al-Ghazali terhadap Taklik Talak dalam Hukum Positif Indonesia - Muhamad Abduh; Tutik Hamidah (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2021)
This article discusses the taklik talak regulation in Indonesia from the maslahah theory point of view. The essence of the study of maslahah is the application of benefit. The idea of mashlahah theory that researcher applies is from Imam al-Ghazali perspective. Actually, taklik talak in positive law of Indonesia is adopted directly from the classical fiqh resources. In the sense that taklik talak from classical fiqh is the main ingredient and element regarding the formation of these regulations into positive law in Indonesia, however, it seems that its application is slightly different from the provisions of taklik talak in classical fiqh. This research is included in normative research using a library research approach and using source materials in the form of books, journals, and websites related to the research focus. By conducting studies on various aspects of benefit in taklik talak applied in Indonesia, it indirectly creates unoriginality with its source in classical fiqh. Through this mashlahah point of view, the author wants to dig deeper into taklik talak in Indonesia. The result of this study explains that the concept of mashlahah or benefit has a role that supports the taklik talak regulations applied by Indonesia. So even though it has differences with taklik talak which comes directly from classical fiqh, the benefits of taklik talak are appropriate for the Muslims Societies in Indonesia.